2008
DOI: 10.1164/rccm.200709-1322oc
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-enhanced Magnetic Resonance Imaging versus Computed Tomography

Abstract: O(2)-enhanced MRI is effective for pulmonary functional loss assessment and clinical stage classification of smoking-related COPD and quantitative CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…The frequency and spatial extent of signal alterations detected by T1 mapping, oxygen-enhanced T1 mapping and perfusion abnormalities increased from mild to severe COPD, and each showed a moderate agreement with GOLD stage. Despite using a different approach (dynamic oxygen-enhanced MRI delivering relative signal changes) in a prospective multi-center trial, Ohno et al also reported a significant association between the mean relative enhancement ratio during supplementation of 100% oxygen and air flow limitation (FEV1%) in 160 smokers [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The frequency and spatial extent of signal alterations detected by T1 mapping, oxygen-enhanced T1 mapping and perfusion abnormalities increased from mild to severe COPD, and each showed a moderate agreement with GOLD stage. Despite using a different approach (dynamic oxygen-enhanced MRI delivering relative signal changes) in a prospective multi-center trial, Ohno et al also reported a significant association between the mean relative enhancement ratio during supplementation of 100% oxygen and air flow limitation (FEV1%) in 160 smokers [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…84,85 The approach consists in detecting modulations of lung parenchymal proton signals induced by changes in oxygenation levels. 86 Oxygenenhanced MRI has been further explored clinically in smoking-induced COPD patients 87,88 and in asthmatics. 89 Ohno et al 88 showed recently in a large cohort of individuals that dynamic O 2 -enhanced MRI is as efficacious as thin-section multidetector-row CT to quantify COPD-related changes in patients (Figure 17.7).…”
Section: Ventilationmentioning
confidence: 99%
“…There have been substantial advances in functional pulmonary MRI in the last few decades from imaging gases dominated by polarized noble gases and from tissue MRI, notably from the effect of breathing pure oxygen on the tissue T 1 . The present study is anatomical in comparison.…”
Section: Introductionmentioning
confidence: 96%
“…21 There have been substantial advances in functional pulmonary MRI in the last few decades from imaging gases 24 dominated by polarized noble gases [25][26][27][28][29][30][31] and from tissue MRI, notably from the effect of breathing pure oxygen on the tissue T 1 . [32][33][34][35][36][37][38][39][40] The present study is anatomical in comparison. We want good images of the tissue and pathologies themselves (s.s., the protons therein).…”
Section: Introductionmentioning
confidence: 99%